Pengaruh Revolusi Industri 4.0 Terhadap Hubungan Komunikasi Antarmanusia Dalam Implikasi Perubahan Sosial Di Era Digital - Alivia Fitri Salsabila; Rehnaningtyas Rehnaningtyas (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to study the Industrial Revolution 4.0 in Human Communication Relations and the Implications of Social Change in the digital era. Industrial Revolution 4.0 has brought major changes in the way people communicate and interact in the digital era. Revolution 4.0 refers to industrial and technological changes characterized by the use of digital technologies such as artificial intelligence, the Internet of Things, and big data. The aim of this research is to study the impact of social changes brought by the industrial revolution 4.0 on human communication relations. The research method used is qualitative, namely collecting data from various trusted sources. The research results show that the Industrial Revolution 4.0 has had a significant impact on industrial and communications technology, such as cyber-physical systems, digitalization and automation. The impact of social change includes changes to the education system, the role of teachers as educators, and the skills needed in the Education 4.0 era. Apart from that, the Industrial Revolution 4.0 will also influence the social characteristics of society, such as an increase in the number of alliances and organizations in cyberspace, international movement of labor and capital and growing cooperation between the private sector and government. The conclusion of this research highlights that the digital revolution has positive and negative impacts on society. Therefore, efforts need to be made to minimize the negative impacts and maximize the positive impacts of the digital revolution.